Regional differences in police officer misperceptions: a quasi-experimental evaluation of sexual assault investigations training in Kentucky - Lapsey, David S. (Policing and society, 2025)
Our study fills an important research gap by investigating the differences in myths and misperceptions about sexual assault survivors among police officers (N = 388) and evaluating the effects of sexual assault investigations training across geographic regions. First, we assessed police officers’ pretraining rape myth acceptance and misperceptions of crime victim reporting behaviours. Second, we used a Solomon four-group quasi-experimental design to assess pretesting effects and evaluate the effect of training and jurisdiction type on officers’ adherence to rape myths and misperceptions of trauma. We used Ordinary Least Squares (OLS) models to evaluate regional differences in officers’ adherence to myths and misperceptions about survivors, the main effects of training, effects of training when considering jurisdiction type, and the moderating effects of officer jurisdiction type on training outcomes. Results showed lower pretraining scores for urban/suburban officers and significant improvements in post-training scores across geographic regions. In addition, officer jurisdiction type failed to moderate –change—the relationship between training and outcomes. This research improves our understanding of officer misperceptions regarding sexual assault survivors and the impact of specialised sexual assault training in different geographic contexts.